Study of the Arctic mesopelagic layer with vessel and profiling multifrequency acoustics. (March 2020) - Dias Bernardes, Inês; Ona, Egil; Gjøsæter, Harald
Highlights: Multifrequency data can be obtained in the DSL with a profiling probe. Mesopelagic fish densities shown to be marginally higher with the probing system. Zooplankton can be measured with the TS-probe to 600 m. In situ target strength can be measured for mesopelagic fish and macrozooplankton. Abstract: The range limitation (>200 m) for high-frequency echosounders does not allow for complete multifrequency studies of the mesopelagic layers from vessel-mounted echosounders. The layers of mesopelagic fish and zooplankton in the Arctic region north of Svalbard (Spitsbergen) were studied using vessel-mounted echosounders and a profiling acoustic probe, using 38, 120, 200 and 333 kHz. Volume density estimates of mesopelagic fish have shown to be marginally higher with the probing system in relation with measured from the vessel-mounted echosounders at 38 kHz. This shows that the swimbladder resonance phenomenon is not occurring in low density layers with limited vertical migration. The use of the profiling probe allowed densities to be calculated with an in situ measured target strength (TS) . In depths >200 m where high-frequency hull-mounted transducers cannot effectively reach, the profiling system measured a mixture of krill and amphipods down to 600 m. Vertical profiles of measured target categories, from vessel transducers and from the probing system are compared in relation to the biological sampling conducted during the survey. Profiling acoustics are shown to be a valuable tool to address some limitations in the current surveying methods for studying mesopelagic layers beyond the reach for high-frequency vessel-mounted systems.